Glucagon-Like Peptide-1 Analog, Liraglutide, Delays Onset of Experimental Autoimmune Encephalitis in Lewis Rats - DellaValle, Brian; Brix, Gitte S.; Brock, Birgitte; Gejl, Michael; Landau, Anne M.; Møller, Arne; Rungby, Jørgen; Larsen, Agnete (Frontiers in Pharmacology, 2016)
Abstract Introduction: Recent findings indicate that metabolic disturbances are involved in multiple sclerosis (MS) pathology and influence the susceptibility to treatment, directing attention towards anti-diabetic drugs such as metformin and pioglitazone. Liraglutide, a drug of the glucagon-like peptide-1 (GLP-1) family, is also anti-diabetic and weight-reducing and is moreover, directly neuroprotective and anti-inflammatory in a broad spectrum of experimental models of brain disease. In this study we investigate the potential for this FDA-approved drug, liraglutide, as a treatment for MS by utilizing the experimental model, experimental autoimmune encephalitis (EAE). Methods: EAE was induced in 30 female Lewis rats that subsequently received twice-daily liraglutide (200 µg/kg s.c.) or saline. Healthy controls were included (saline, n=6, liraglutide, n=7). Clinical score and weight were assessed daily by blinded observers. Animals were killed at peak disease severity (day 11) or if exceeding humane endpoint (clinical score ≥4). Protein levels of manganese superoxide dismutase (MnSOD), amyloid precursor protein (APP, and glial fibrillary acidic protein (GFAP) were determined. Results: Liraglutide treatment delayed disease onset (group clinical score significantly >0) by two days and markedly reduced disease severity (median clinical score 2 vs. 5; p=0.0003). Fourteen of 15 (93%) of vehicle-treated rats reached the humane endpoint (clinical score ≥4) by day 11 compared to 5 of 15 (33%) of liraglutide-treated rats (p=0.0004). Liraglutide substantially increased the mitochondrial antioxidant MnSOD (p<0.01) and reduced the neurodegenerative marker APP (p=0.036) in the brain. GFAP levels were not significantly changed with drug treatment (p=0.09) Conclusion: We demonstrate, for the first time, that liraglutide treatment delays onset of EAE in Lewis rats and is associated with improved protective capacity against oxidative stress. These data suggest GLP-1 receptor agonists should be investigated further as a potential therapy for MS. Keywords: GLP-1, EAE, Multiple Sclerosis, liraglutide, MS, MnSOD, APP